Novel synaptobrevin‐1 mutation causes fatal congenital myasthenic syndrome. Issue 2 (16th January 2017) - Shen, Xin‐Ming; Scola, Rosana H.; Lorenzoni, Paulo J.; Kay, Cláudia S. K.; Werneck, Lineu C.; Brengman, Joan; Selcen, Duygu; Engel, Andrew G.
Abstract: Objective: To identify the molecular basis and elucidate the pathogenesis of a fatal congenital myasthenic syndrome. Methods: We performed clinical electrophysiology studies, exome and Sanger sequencing, and analyzed functional consequences of the identified mutation. Results: Clinical electrophysiology studies of the patient revealed several‐fold potentiation of the evoked muscle action potential by high frequency nerve stimulation pointing to a presynaptic defect. Exome sequencing identified a homozygous c.340delA frameshift mutation in synaptobrevin 1 (SYB1), one of the three SNARE proteins essential for synaptic vesicle exocytosis. Analysis of both human spinal cord gray matter and normal human muscle revealed expression of the SYB1A and SYB1D isoforms, predicting expression of one or both isoforms in the motor nerve terminal. The identified mutation elongates the intravesicular C‐terminus of the A isoform from 5 to 71, and of the D isoform from 4 to 31 residues. Transfection of either mutant isoform into bovine chromaffin cells markedly reduces depolarization‐evoked exocytosis, and transfection of either mutant isoform into HEK cells significantly decreases expression of either mutant compared to wild type. Interpretation: The mutation is pathogenic because elongation of the intravesicular C‐terminus of the A and D isoforms increases the energy required to move their C‐terminus into the synaptic vesicle membrane, a key step for fusion of the synaptic vesicle with the presynaptic membrane, and because it is predicted to reduce expression of either isoform in the nerve terminal.